Human Agency in the Age of Technology - Reviers, Nina; Vercauteren, Gert; Neves, Joselia (Journal of Audiovisual Translation, 2024)
The landscape of audiovisual translation (AVT) is rapidly evolving due to AI and language technologies that are fundamentally reshaping production dynamics, workflows and professional profiles. This special issue examines the impact of these advancements on the media localization industry and, in particular, the professionals involved. Contributions in this special issue explore challenges faced by subtitlers in template-driven environments and the effectiveness of automatic speech recognition (ASR) tools, underscoring the need for human intervention to maintain quality. Additionally, the articles address broader social movements emphasizing representation and inclusion in media accessibility. Collectively, this issue illustrates that while technology offers efficiency, the irreplaceable role of human expertise in creativity and contextual adaptation remains crucial. The future of AVT will depend on a collaborative approach, where technological advancements complement human insight to enhance the quality and accessibility of translated media.